Pseudoaneurysm of the Anterior Tibial Artery following Tibio-Talar-Calcaneum Fusion with a Retrograde Nail: A Rare Case and Literature Review - Simon Craxford; Saravana V. Karuppiah; Stephen Milner (Case Reports in Orthopedics)
This study reports the case of an 87-year-old woman who presented with a nonresolving haematoma 13 weeks following tibiotalar arthrodesis surgery on her right ankle using a retrograde nail. This was revealed by angiography to be a pseudoaneurysm of the anterior tibial artery. The patient subsequently underwent endovascular stenting of the pseudoaneurysm and has had a successful recovery. This case highlights the need for awareness of both the normal arterial supply to the leg and ankle as well as the potential for anatomical variations. Arterial variation may be as high as 6.7% based on published findings from cadaveric studies. As pseudoaneurysm is a rare complication, a high index of suspicion is needed in order to avoid a missed or delayed diagnosis. We urge surgeons to keep in mind the potential for pseudoaneurysm when a patient presents with a nonresolving haematoma and arrange appropriate further investigations as needed.